Concerted Efforts Are Needed to Control and Mitigate Antibiotic Pollution in Coastal Waters of China - Huaijun Xie; Jing Du; Jingwen Chen (MDPI AG, 2020)
Antibiotics have been applied for decades and antibiotic pollution is of great concern due to the risk for promoting resistant genes. Human activities such as mariculture and land-based discharge can lead to the antibiotic pollution in coastal area and it is of importance to assess the pollution and risks of antibiotics in this area. In this mini-review, the pollution status of antibiotics in Chinese coastal waters is summarized and some perspectives are put forward for future efforts to mitigate the pollution.